Reduced fasting-induced activation of hypothalamic arcuate neurons is associated with hyperleptinemia and increased leptin sensitivity in obese mice - Becskei, Csilla; Lutz, Thomas A.; Riediger, Thomas (American journal of physiology. Regulatory, integrative and comparative physiology, 2010)
Fasting increases c-Fos expression in neuropeptide Y (NPY) neurons of the hypothalamic arcuate nucleus (ARC) in lean, but not in hyperleptinemic mice with late-onset obesity (LOO). Although obesity is associated with leptin resistance, we hypothesized that under fasting conditions, leptin sensitivity might be restored and that hyperleptinemia may counteract the neuronal response to fasting. We investigated whether the reduced fasting response of ARC neurons in LOO is paralleled by an increase in leptin sensitivity, as measured by leptin-induced STAT-3 phosphorylation. To assess leptin's role in the modulation of the fasting-induced ARC activation, we investigated c-Fos responses and hormone and metabolite levels in hyperleptinemic diet-induced obese (DIO) and in leptin-deficient ob/ob mice. Leptin induced a stronger STAT-3 phosphorylation in fasted LOO and lean mice than in ad libitum-fed animals. Similar to LOO, hyperleptinemic DIO mice showed no c-Fos response after fasting, while ob/ob mice showed a stronger response than lean control mice. Mimicking hyperleptinemia by repeated leptin injections in lean mice during fasting attenuated the fasting-induced c-Fos expression. Our findings indicate that high leptin levels prevent the fasting-induced activation of ARC neurons in mice. Moreover, leptin sensitivity is dynamic in obese subjects and depends on the feeding status. During short-term increases in leptin sensitivity, e.g., during fasting, leptin signaling appears to be effective, even in hyperleptinemic obesity. As reflected by the blockade of the fasting-induced ARC activation, fasting seems to interfere with the responsiveness of the ARC to signals related to the status of energy intake.